Economics lab : an intensive course in experimental economics - Friedman, Daniel, 1947- (Routledge advances in experimental and computable economics., 2004)
This textbook sketches the history of experimental economics before moving on to describe how to set up an economics experiment and to survey selected applications and the latest methods.